2005
DOI: 10.1021/es0483589
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Hydroxycarbonyl Products of the OH Radical Initiated Reactions of C5−C8n-Alkanes in the Presence of NO

Abstract: Ambient measurements of polycyclic aromatic hydrocarbons (PAHs) and nitro-PAHs were carried out during August 2002 and January 2003 in Los Angeles, CA, a source site and in Riverside, CA, a downwind receptor site approximately 90 km to the east of Los Angeles. Atmospheric concentrations of PAHs and nitro-PAHs are of interest because both of these compound classes include potent mutagens and carcinogens. To augment our current understanding of atmospheric formation of nitro-PAHs, four sampling periods were empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 35 publications
4
97
0
Order By: Relevance
“…However, this composition is explained by the products of alkane oxidation by OH (23,24,(31)(32)(33). In the NO x regime (>30 ppt NO, likely for combustion emissions), major firstgeneration products from reactions of linear alkanes larger than ∼C 10 -C 15 are ∼30% monoalkyl nitrates, ∼55% 1,4-hydroxycarbonyls, and ∼15% 1,4-hydroxynitrates.…”
Section: Resultsmentioning
confidence: 99%
“…However, this composition is explained by the products of alkane oxidation by OH (23,24,(31)(32)(33). In the NO x regime (>30 ppt NO, likely for combustion emissions), major firstgeneration products from reactions of linear alkanes larger than ∼C 10 -C 15 are ∼30% monoalkyl nitrates, ∼55% 1,4-hydroxycarbonyls, and ∼15% 1,4-hydroxynitrates.…”
Section: Resultsmentioning
confidence: 99%
“…first (8) where t is the delay time between the photolysis and the probe beams, k first is the pseudo first-order rate coefficient, and k is the second-order rate coefficient for the 4H2B + OH reaction. In order to avoid the accumulation of photolysis or reaction products, the experiments were carried out under flow conditions so that the gas mixture in the cell was renewed between two consecutive photolysis pulses.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The products are 1,4-hydroxynitrates (1,4HN) [5] and 1,4-hydroxyalkoxy radicals that primarily undergo a reverse isomerization and react with O 2 to form 1,4-hydroxycarbonyls (1,4HC) [6]. AN, 1,4HN, and 1,4HC have been measured in the gas-phase for reactions of C 7 -C 10 alkanes, with yields of approximately 0.2, 0.05, and 0.5 (Reisen et al 2005) and with no other observed products. AN and 1,4HN yields are probably closer to ∼0.3 (Arey et al 2001) and ∼0.15 (Lim and Ziemann 2005) for reactions of larger alkanes.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…The only other known potential effect of NH 3 on the reaction mechanism shown in Figure 2 is that it can bind to hydroxyperoxy radicals and thereby increase the formation of hydroxyalkoxy radicals from the reaction with NO (Matsunaga and Ziemann 2009), in this case at the expense of 1,4HN, the reaction co-product. This would increase the yield of 1,4HC (by possibly 10-20% from ∼0.5 if no 1,4-HN were formed (Reisen et al 2005;Lim and Ziemann 2005)) and also enhance CHA formation. Although we cannot rule out the possibility that NH 3 altered the reaction of 1,4-hydroxyperoxy radicals with NO, any impact appears to have been minor.…”
Section: Effect Of Ammoniamentioning
confidence: 99%